TEACHING STUDENTS’ READING COMREHENSION BY USING GENERATING INTERACTION BETWEEN SCHEMATA AND TEXT (GIST) STRATEGY - Wisa Rahmawati; Finny Anita; maliqul hafis (IKIP PGRI Pontianak, 2020)
The thesis was a pre-experimental research in form of one group pre-test post-test design conducted in one of junior high school in west borneo which consisted of 31 students’ and it was examined with cluster random sampling technique. The technique of data collection applied in this research was measurement technique. The data were collected through multiple choice test. The pre-test and post-post-test were conducted in order to collect the data from the students. The data were analyzed by using descriptive statistic. The research finding showed that GIST strategy was effective on reading comprehension, it was proved by the mean score during pre-test and post-test were 52, 88 and 63, 30 which meant that there were difference before and after treatment. Lastly it was proved by t-test value, sig value was smaller than α (0, 00 0, 05) which meant that Ha was accepted. The effect of the use GIST strategy was moderate effect level based on the Cohen’s effect. It was 0, 56 which meant that moderate effect to increase students’ reading comprehension.Keywords: Generating Interaction between Schemata and Text (GIST), Reading Skill, and Pre-Experimental Research.